Application of Johnson disribution to the problemof aerospace images classification; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 5 - Burkatovskaya Yu. B. Yuliya Borisovna; Markov N. G.; Morozov A. S.; Serykh A. P. (Control, computer engineeringand information science, 2007)
Заглавие с титульного листа